The attitudes of the great powers towards the early years of the Gulf War between Iraq and Iran 1980-1988 - خالد العلي; إبراهيم علاء الدين; رامي الضللي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The Iran-Iraq war was a surprising event, as Iraq started shortly after the outbreak of the Islamic Revolution in Iran, after it canceled its recognition of the border demarcation agreement that had been signed between the two parties and was known as the Algiers Agreement. The Shah, who is the main ally of the United States in the region, and because it will weaken Iraq, which is a major ally of the Soviet Union, while it came at the appropriate moment for the United States. Regardless of what was left behind by that war, both countries rushed to try to grab its threads and direct it in accordance with the interests of each of them and considers the United States The most prominent beneficiaries with some of the benefits that the Soviets reaped from an economic point of view, especially after the increase in oil prices and the increase in arms sales to both parties.